Correlation of Smac/DIABLO protein expression with the clinico-pathological features of breast cancer patients - Pluta, Piotr; Cebula-Obrzut, B.; Ehemann, Volker; Pluta, A.; Wierzbowska, A.; Piekarski, J.; Bilski, A.; Nejc, D.; Kordek, R.; Robak, T.; Smolewski, P.; Jeziorski, A. (Neoplasma, 2011)
Smac/DIABLO protein promotes caspase-dependent apoptosis by inhibition of inhibitor of apoptosis protein (IAP) family members. The role of Smac/DIABLO in breast cancer has not been yet established. Therefore, the aim of the study was to assess the expression of this protein in tumor cells from breast cancer patients. The expression of Smac/DIABLO was analyzed in 62 breast cancer patients by flow cytometry. The obtained results were compared with expression of this protein in benign breast tumor tissue, which served as the control (11 patients with fibroadenoma). Expression of caspase-3 proteins in breast cancer was also evaluated. Smac/DIABLO expression in breast cancer was correlated with clinical and pathological data. Although the expression of Smac/DIABLO protein was found in all examined samples of both the breast cancer and fibroadenoma patients, the median expression of Smac/Diablo in breast cancer was significantly lower than in the control (39.1% vs. 48.1%; p=0.0047). Smac/DIABLO expression correlated with expression of caspase-3 (p=0.000008). In pT1 breast cancer patients, expression of Smac/DIABLO protein was higher than in those with pT2-3 (p=0.02). Diffuse cancer infiltration significantly correlated with lower expression of Smac/DIABLO protein (p=0.02). Moreover, there was a loose correlation between low expression of Smac/DIABLO protein and cancer embolus in minor blood and lymphatic vessels (p=0.08). Our results indicate that expression of Smac/DIABLO inversely correlates with the tumor stage, which may suggest that this protein may play an important role in the breast cancer development.
Gesehen am 23.12.2022
Die DOI funktioniert nicht (festgestellt am 23.12.2022)